Uso de bioinsecticidas en el control del gusano cogollero (Spodoptera frugiperda) en el cultivo de maíz (Zea mays l) en condiciones controladas (Laboratorio). - Suárez Chang, Mario Cristhian (2015)
At present agricultural production systems emphasize the preservation of the environment, as the excessive use of insecticides of chemical origin devoid of previous technical assistance, rather than resolve, has produced severe damage to the productivity of agriculture, humans and nature. Therefore conducted this research in order to evaluate the effect of three bio-insecticides on budworm in laboratory conditions, for which three bio-insecticides were studied: pyroligneous acid, neem and snuff in doses of 125, 100 and 75 cc / l each. Quito km was conducted this test in the microbiology laboratory at the State Technical University of Quevedo, s Manuel Alvarez Campus, located at Av.. 1 1/2 via Quevedo - Santo Domingo de los Tsáchilas. A completely randomized design was used with factorial arrangement 3 x 3 in 3 replications. Based on the analysis and interpretation was observed that: the bio-insecticides Neem and snuff in doses of 125 cc / l showed high mortality rates with 97 and 93% respectively during the five days of the trial which you can conclude that these products can control this pest without polluting the environment; the pyroligneous acid in doses of 125 cc / l killed 80% of the larvae under study. Generally the neem-based insecticide and snuff not differ significantly with mortality rates of 82 and 83%, in that order. Considering the results we can point out that it is possible to control the budworm with bio-insecticides as long as applications are timely made, thus causing the least possible impact on the environment.